Electrically-induced mass transport in a multiple pin-plate electrohydrodynamic (EHD) dryer. (October 2017) - Shi, C.A.; Martynenko, A.; Kudra, T.; Wells, P.; Adamiak, K.; Castle, G.S.P.
Abstract: A theoretical approach to quantify the electric field intensity, space charge density and mass transport in a multiple pin-plate electrohydrodynamic dryer has been developed. It was found that: (i) the corona onset voltage depends largely on the electrode geometry, decreasing for smaller gaps and larger spacing between pins, (ii) the charge flow rate (convection current) depends on voltage, gap and electrode geometry, and (iii) airflow mass flux generated by multiple-pin electrode is proportional to the voltage and square root of electric current. The theoretical model of electrically-induced airflow predicts velocity profile and occurrence of aerodynamic vortices in a single channel of flowing air. The model has been experimentally validated in drying experiments with wet paper tissue. Drying with 2 × 2 cm electrode showed good correlation between model-predicted air mass flux and water transport from the wet material. Smaller spacing between pins (1 × 1 cm) significantly affected charge distribution, aerodynamics of airflow and mass transfer. Highlights: Theoretical model of corona discharge for multiple pin-plate dryer has been developed. Parabolic curve well describes the relationship between current and voltage. Simulation and experiment showed strong coupling between charge and mass transport. Aerodynamic vortices significantly affect mass transport.